Stimulasi Kreasi dan Inovasi Siswa SMPN 1 Meulaboh Via Pembuatan Logo Produk dengan Adobe Photoshop - Zuhri, Al; Khairina, Ulfa; Nurdin, Hanifah; Ismiati, Ismiati; Kurniawan, Rafli; Riwanda, Aisha; Chusyeri, Imam; Murdial, Feni; Naja, Khairul (Universitas Malikussaleh, 2024)
Technological advances have simplified many fairies in human life, ranging from the social, business, political, and even educational realms. One form of technology that plays an important role in facilitating and helping humans today is computers. The presence of computers has boosted the emergence of various applications that play a very important role in supporting human work such as in producing graphic design products. Graphic design works are certainly no longer a foreign entity in life, starting from the clothes worn, the packaging design of the daily food/beverages consumed, and even the logos of the electronic objects purchased are also inseparable from the touch of graphic design. That is the value and meaning of the existence of graphic design works today for humans. Graphic design, in addition to being able to support human work to open up business opportunities, can also be a medium to foster a creative and innovative attitude for anyone who has a desire for it. On that basis, the team also considers it necessary to facilitate training such as this service to encourage the emergence of creativity and innovation in students by making SMP Negeri 1 Meulaboh, West Aceh Regency, Aceh Province as the target of this service. The steps taken in this service are divided into three time sessions, namely the beginning, middle, and end. The presentation of the material was carried out by applying the concept of Think Pair Share. From the results of the thorough evaluation, the following records were obtained: (1). Students have a high interest in these kinds of activities; (2). There is a drastic increase in knowledge and ability in students after the activity is completed from before who do not know at all and have never heard of graphic design; and (3). After the presentation of the material and demonstration, students have been able to independently practice how to design a logo using the professional application Adobe Photoshop, even if they are not very skilled.